APPLICATION OF MOBILE TECHNOLOGIES IN ADVANCED TRAINING - Sherzod Xujakulov (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2021)
This article discusses the content, advantages and peculiarities of teaching on the basis of mobile technologies, one of the promising areas of education.